Use of instruments of environmental marketing concept in sustainable development of the region - C.I. Myshko; O.D. Lendyel; V.I. Yarema (Marketing i Menedžment Innovacij, 2011)
In article deals the main directions of environmental marketing for the effective implementation of sustainable development. The role of state bodies, enterprises, organizations and the public in implementing environmental marketing.